Are treatment results for eating disorders affected by ADHD symptoms? A one‐year follow‐up of adult females. (2nd May 2018) - Svedlund, Nils Erik; Norring, Claes; Ginsberg, Ylva; von Hausswolff‐Juhlin, Yvonne
Abstract: Objective: To explore the influence of self‐reported Attention Deficit Hyperactivity Disorder (ADHD) symptoms on recovery rate at 1‐year follow‐up in an unselected group of patients in a specialized eating disorder (ED) clinic. Methods: Four hundred forty‐three adult females with an ED were assessed with the ADHD Self‐Report Scale for Adults (ASRS‐screener), and for demographic variables and ED symptoms. Recovery was registered at 1‐year follow‐up. Results: A high degree of ADHD symptoms at baseline was predictive for nonrecovery of ED at 1‐year follow‐up in patients with loss of control over eating, bingeing, or purging. The presence of inattentive ADHD symptoms was stronger associated with nonrecovery than hyperactive/impulsive symptoms. Conclusions: A high degree of ADHD symptoms may have a negative impact on recovery in ED. Screening/diagnostic evaluation of ADHD in all loss of control over eating/bingeing/purging ED patients and studies of the effect of implementing ADHD‐treatment strategies in this patient group are recommended.